2020
DOI: 10.1136/bmjopen-2020-036870
|View full text |Cite
|
Sign up to set email alerts
|

Association between different coping styles and health-related quality of life in people with Parkinson’s disease: a cross-sectional study

Abstract: ObjectiveTo describe overlapping coping strategies in people with Parkinson’s disease.DesignCross-sectional, cohort study.SettingMonocentric, inpatient and outpatient, university hospital.ParticipantsTwo-hundred participants enrolled, 162 patients with Parkinson’s disease (without dementia) analysed.Primary and secondary outcome measuresPrevalence of different coping styles according to the German Essen Coping Questionnaire. Association between coping, sociodemographic and clinical parameters (Movement Disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…However, the current results also suggest that there is some mix of them as the content in each of the patterns is not purely passive or purely active. This is in line with evidence of overlap between passive and active styles found by Liebermann and colleagues [ 26 ] in a recent study. These two coping patterns also resemble findings of an early study by Dakof and Mendelsohn [ 40 ] where two of four clusters emerging from analysis of interview data with PD patients were identified as “Passive and resigned” and “Sanguine and engaged”, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the current results also suggest that there is some mix of them as the content in each of the patterns is not purely passive or purely active. This is in line with evidence of overlap between passive and active styles found by Liebermann and colleagues [ 26 ] in a recent study. These two coping patterns also resemble findings of an early study by Dakof and Mendelsohn [ 40 ] where two of four clusters emerging from analysis of interview data with PD patients were identified as “Passive and resigned” and “Sanguine and engaged”, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Longitudinal studies on stability and change in coping in later life in general have revealed the need to consider not only functional strategies but also coherent coping styles [ 19 , 25 ]. Research findings from both cross-sectional and longitudinal studies on coping with PD have also provided evidence on the need to address patterns as well as overlapping and mixed styles of coping [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following demographical and PD-related data were collected: age, gender, educational level, marital status, living situation, and professional activity. In addition the following parameters were assessed, because they were found to be related to coping in PD in an earlier study [ 1 ]: The Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale III (MDS-UPDRS III) [ 24 ], the revised nonmotor symptoms questionnaire (NMS-Quest) [ 25 ], and Hoehn and Yahr staging were used to evaluate motor and nonmotor symptoms; cognition was assessed using the MoCa and depression was assessed using the Beck Depression Inventory II (BDI-II). The Medical Outcomes Study (MOS) Short Form 36 (SF-36) was used to measure health-related QoL [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…People with Parkinson’s disease (PPD) have various methods for coping or dealing with disease and symptoms [ 1 , 2 ]. Among others, pain is one of the most bothersome nonmotor problems in PD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…PWP's who are more knowledgeable about the disease and implement suitable strategies, cope better with the disease (Lorig & Holman, 2003), experience less depression, develop an internal locus of control, and improved QOL. (Liebermann et al, 2020). As one of the patients in the program explained: " I have gained awareness of my limitations alongside the confidence that everything can be done".…”
Section: Discussionmentioning
confidence: 99%